PENGARUH SUHU DAN WAKTU TERHADAP KEKUATAN TARIK DENGAN PENGUJIAN TERMAL MEKANIS PADA BELT CONVEYOR 2 PLY - Muslih Muhammad; Hari Arbiantara; Ahmad Adib Rosyadi (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2015)
Belt is a major component that directly contact with the material and also it is a component that can be worn out in a conveyor system. Along with its production capacity and lack of conveyor belt proper maintenance, a conveyor belt will experience a variety of obstacles or problems. The problem that often occurs is the torning belt. To overcome the problems, belt splicing is necessary to do. Hot splicing method is one method that can help connecting the belt. Hot splicing method utilizing heat, time and pressure to connect the belt. The purpose of this study is to determine the influence of temperature and timing of belt splicing against tensile strength with thermal mechanical testing. The method used in this study is the experimental method, a method used to test the effect of a treatment on the object under study. Experiments carried out at a temperature variation of grafting ( 130 ºC, 145 ºC and 160 ºC) and the variation of the connection time for 20 minutes , 30 minutes and 40 minutes . The results Showed the highest strength values of 5:14 MPa at a temperature of 130 ºC splicing and connecting time of 40 minutes. Keywords: Belt Conveyor, Splicing Temperature and Splicing Time.